AB0910 Once-Weekly Teriparatide is Effective for Glucocorticoid-Induced Osteoporosis Patients with Collagen Diseases. (9th June 2015) - Seno, T.; Yamamoto, A.; Kukida, Y.; Tominaga, A.; Kida, T.; Nakabayashi, A.; Fujioka, K.; Nagahara, H.; Murakami, K.; Fujii, W.; Oda, R.; Kubo, T.; et al.
Abstract : Background: Glucocorticoid-induced osteoporosis (GIOP) patients are at very high risk of fractures. Unfortunately, only a small minority of GC users receive effective preventive, diagnostic, and therapeutic interventions. Intermittent administration of teriparatide (TPTD) is the only currently available anabolic agent to stimulate osteoblast activity. Daily TPTD was more efficacious than alendronate in increasing lumbar spine BMD in men and pre- and postmenopausal women. Recently, once-weekly TPTD was provided, which had both rapid and powerful anti-fracture efficacy. It has unique feature; serum NTx is decreasing after administration for patients with primary osteoporosis contrast to daily TPTD. Once-weekly TPTD is expected to be effective for GIOP, but it has not been reported. Objectives: To examine the efficacy of once-weekly TPTD for patients with GIOP and collagen diseases. Methods: We registered GIOP patients with collagen diseases treated with once-weekly TPTD at our department. They were treated with PSL for at least 6 months and had inadequate response for bisphosphonates. We measured YAM (Young Adult Mean), serum NTx (cross-linked N-terminal telopeptides of type I collagen), BAP (Bone alkaline phosphatase), Ca, FRAX at baseline, 6 months, 12months and 18 months after starting once-weekly TPTD. We calculated the change rate of those values to baseline. The continuous variables were compared using ANOVA and Wilcoxon matched-pairs single rank test. Results: 12 GIOP patients with collagen diseases were registered into this study, and 9 patients completed (6 systemic lupus erythematosus, 2 rheumatoid arthritis, 1 adult onset still disease; 7 female, 2 male; Age 57.4±11.1). Only one new fracture event, that was lumbar compression fracture, occurred during the study period despite the patient had many fractures before this treatment. The change rate of lumbar spine YAM was significantly improved at 18 months ( p =0.041, ANOVA; p =0.019, Wilcoxon matched-pairs single rank test). Femoral neck YAM ( p =0.477, ANOVA), serum NTx ( p =0.555), BAP ( p =0.936), Ca and FRAX were not significantly changed. Interestingly, the change rate of serum NTx was increased during this GIOP study despite the rate was decreased in primary osteoporosis previously reported. Conclusions: Our study shows that once-weekly teriparatide is effective for GIOP patients with collagen diseases, and its dosing period needs 18 months. Mean % change of serum NTx was increased in GIOP patients in spite of primary osteoporosis. References: Bone 2006;39:244–52. J Bone Miner Res 2010;25:472–81. Osteoporos Int 2009;20:2095–104. J Bone Miner Metab 2004;22:569–76. Disclosure of Interest: None declared